1972
DOI: 10.1136/gut.13.11.859
|View full text |Cite
|
Sign up to set email alerts
|

Faecal ammonia and pH during lactulose administration in man: comparison with other cathartics

Abstract: SUMMARY The effect of lactulose on faecal pH and ammonia has been studied in three normal subjects with the aid of dialysis of faeces in vivo. Observations were also made with sodium sulphate and the two hexahydric alcohols, mannitol and sorbitol, given in doses sufficient to cause a similar increase in stool weight.All four cathartics rendered the stool more acid, but there was no increase in the concentration of faecal ammonia. Lactulose, despite increasing faecal volume, did not cause an increase in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

1974
1974
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…The present results suggest that acceptable doses of lactulose will not consistently reduce faecal pH. Agostini et al (1972) showed that, even when faecal pH was lowered by lactulose, there was no demonstrable increase in the faecal excretion of ammonia. It seems unlikely that the trapping of ammonia in an acid stool is relevant in this context.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…The present results suggest that acceptable doses of lactulose will not consistently reduce faecal pH. Agostini et al (1972) showed that, even when faecal pH was lowered by lactulose, there was no demonstrable increase in the faecal excretion of ammonia. It seems unlikely that the trapping of ammonia in an acid stool is relevant in this context.…”
Section: Discussioncontrasting
confidence: 47%
“…In the third subject, the faecal volume was more than doubled, compared with the control period, and the mean pH was significantly reduced by 0.7 unit. In clinical trials of patients with hepatic encephalopathy, much more striking acidification of faeces has been reported in some studies (Elkington et al, 1969;Bircher et al, 1971) but the dose of lactulose used was generally greater than that used by Agostini et al (1972) and the stool volumes were probably larger. Zeegen et al (1970) measured the pH of faecal dialysates and faecal volume in four subjects taking lactulose and extremely variable results were obtained.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The amount of urinary secondary amine was also unchanged during the high fibre period. Agostini et al [1] showed that the amount of urea hydrolysed in the colon by the gut flora was not reduced by the administration of dietary lactulose at a dose high enough to give two stools per day and a fecal pH of 5-6; this is despite the fact that the transit time must have been reduced considerably from the normal. There is certainly no support, therefore, for the contention that a decreased transit time necessarily results in decreased bacterial action on the gut contents.…”
Section: A Fast Transit Time Reduces the Time Available For Bacterialmentioning
confidence: 86%
“…Recent experimental findings [10][11][12], in agreement with the nonionic diffusion of ammonia, tend to confirm that lactulose decreases ammonia resorption by acidifying the colonic content and thereby lowering the intralumen proportion of nonionized ammonia. However, this generally accepted mechanism contradicts the inability of lactulose to increase the absolute quantity of ammonia in the feces [13].…”
mentioning
confidence: 93%